Characteristic Features of the Chinese Marxism's Formation: Key Philosophical and Socio Political Foundations of Rese - Nataliia Yarmolitska; Katherine Gan (International Society of Philosophy and Cosmology, 2022)
In this article, the authors analysed the history of the origin and formation of Marxism in China. An analysis of the main provisions of the philosophical and socio-political foundations of research is proposed. The authors conducted a study of the development process and the main contradictions in the formation of Chineseized Marxism and also tracked the impact it can have on the humanitariandevelopment of modern Ukrainian society. For more detailed coverage of the formation of Chineseized Marxism, the authors conducted a historiographical study of current sources, as well as analysed the literature of the Soviet period, in which the primary attention was paid to the study of the figure of Mao Zedong as the «theoretician of the national revival of China» and the founder of Chineseized Marxism. The main narratives of Soviet studies regarding the «philosophical ideas of Mao Zedong», the «concept of movement and development», the «great leap» and the «cultural revolution» are analysed. In the course of the research, it was established that the vast majority of works of the Soviet period were aimed at criticizing Maoism for anti-communism and nationalism. It was also proved that «Chineseized Marxism» during the entire historical period of its formation did not have much in common with Marxist theory, but was based on the ideas of Marxism-Leninism, Western philosophy, using the teachings of traditional Chinese philosophy as a basis.